2020
DOI: 10.1016/j.chaos.2020.110121
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning methods for forecasting COVID-19 time-Series data: A Comparative study

Abstract: Highlights Developed deep learning methods to forecast the COVID19 spread. Five deep learning models have been compared for COVID-19 forecasting. Time-series COVID19 data from Italy, Spain, France, China, the USA, and Australia are used. Results demonstrate the potential of deep learning models to forecast COVID19 data. Results show the superior performance of the Variational AutoEncoder model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
241
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 403 publications
(266 citation statements)
references
References 38 publications
1
241
0
4
Order By: Relevance
“…Comparing different deep learning algorithms: A comparative study over a number of DNN algorithms in predicting the epidemic is presented in [423] . In this work, simple Recurrent Neural Network (RNN), Long short-term memory (LSTM), Bidirectional LSTM (BiLSTM), Gated recurrent units (GRUs) and Variational AutoEncoder (VAE) algorithms have been studied based on daily confirmed and recovered cases collected from six countries namely Italy, Spain, France, China, USA, and Australia.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%
“…Comparing different deep learning algorithms: A comparative study over a number of DNN algorithms in predicting the epidemic is presented in [423] . In this work, simple Recurrent Neural Network (RNN), Long short-term memory (LSTM), Bidirectional LSTM (BiLSTM), Gated recurrent units (GRUs) and Variational AutoEncoder (VAE) algorithms have been studied based on daily confirmed and recovered cases collected from six countries namely Italy, Spain, France, China, USA, and Australia.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%
“…Accurately predicting the development of new cases can more effectively manage the resulting excess demand in the entire supply chain. Zeroual et al [ 10 ] found that effective management of infected patients has become a challenging problem facing hospitals. Accurate short-term prediction of the number of new infections and recovered cases is essential to optimize available resources and prevent or slow the development of such diseases.…”
Section: Related Workmentioning
confidence: 99%
“…Theorem 1. All the solutions of the system (1) subject to initial condition (2) are positive and bounded in R 3 + , for all t > 0.…”
Section: Positivity and Boundednessmentioning
confidence: 99%
“…Also, the Government of states has implemented lockdown, travel restrictions, quarantine measures and testing to control the disease. Several epidemiological mathematical models [3][4][5][6][7][8][9] have been developed to make the right decisions in these measures. These have highlighted that social distancing intervention to mitigate the epidemic is a key aspect.…”
Section: Introductionmentioning
confidence: 99%